Do Animals' Minds Matter Less, When Meat Gets Personal? Replications of Piazza and Loughnan (2016) in China. Issue 3 (April 2021) - Tian, Qirui; Liu, Xiao-xiao; Zhou, Jiayu; Sun, Tianwen
Piazza and Loughnan found that the high intelligence information about animals leads to higher moral standing judgment except for self-relevant animals. We replicated the original three studies in China. Study 1 finds that the intelligence information about a fictional animal does not affect moral standing judgment or hunting decisions, inconsistent with the original study. By manipulating the intelligence of animals in one's culture (pig) versus in other cultures (tapir or trablan), Study 2 consistently finds that intelligence information does not influence moral standing judgment only for pigs. Study 3 reveals that participants have higher moral standing judgment for pigs from another's perspective but not from one's own perspective, regardless of the intelligence information. These findings partly replicate the original findings, indicating inconsistency in how people apply mind information in judging the moral standing of animals. When animals become self-relevant, intelligence information no longer increases the moral standing of animals.